Nymble: Preventing Misbehaving Customers in Anonymizing Communities (International Journal of Advanced Research in Science, Management and Technology, 2023)
The approach of anonym zing systems guaranteed that clients could get to web administrations with complete privacy maintaining a strategic distance from any conceivable impediment. This game plan where arrangement of switches structure a system, conceal the client's IP address from the server. However misbehaviour of few malpractitioners has left this framework with a proviso where clients make utilization of this obscurity to mutilate mainstream sites. Executives who can't for all intents and purposes obstruct a client utilizing IP location are compelled to close all conceivable hubs that prompt way out. Along these lines deny access to both carrying on and non-behaving users out and out. Thus wind up blocking clients with no bargain to their obscurity. Subsequently we propose a framework which is undogmatic with diverse servers. In this way we go for giving the chairman the privilege to obstruct the malevolent client without blocking the obscurity of the rest.
Keywords: anonym zing networks, blacklisting, symmetric cryptography, Tor, pseudonym, nymble ticket, Anonymous authentication, backward unlinkability, revocation auditability.